THE STUDY OF POVERTY OF TRADITIONAL FISHERMEN HOUSEHOLDS IN BULUH ISLAND KELURAHAN BULUH ISLAND BULANG SUBDISTRICT BATAM CITY RIAU ISLAND PROVINCE - Dita Putri Deffrina; Darwis '; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February, 2017 located in Buluh Island Kelurahan Buluh Island Bulang Subdistrict Batam City Riau Island Province. This study aims to find out the level of income and expenditure of traditional fishermen households, factors causing poverty and survival strategy of traditional fishermen Buluh Island. The method used in this study is survey method with 48 household as respondents determination by simple random sampling. Average income level of fisherman household is Rp.761,979,-/month and the average expenditure of traditional fishing households was Rp.1.236.681,-/month. A factors causing poverty of the most influential traditional fishermen is the factor of human resources, with low level of education the tradisional fisherman can not find alternative job that can help fisherman out of poverty line. While survival strategies commonly practiced by tradisional fisherfolk household are optimizing is to optimize the role of family members, regulating consumption patterns and borrowing to survive poverty.Key word: Income, expenditure, poverty, fishermen.